Reproductive biology of the nest building vizcacheras frog Leptodactylus bufonius (Amphibia, Anura, Leptodactylidae), including a description of unusual courtship behaviour - Faggioni, Gabriel; Souza, Franco; Uetanabaro, Masao; Landgref-Filho, Paulo; Furman, Joe; Prado, Cynthia [UNESP] (British Herpetol Soc, 2017)
We describe the reproductive biology and sexual size dimorphism of a population of the vizcacheras frog Leptodactylus bufonius in the Brazilian Chaco. Reproduction takes place during the rainy months (September-March). During courtship, females emit reciprocal calls and both sexes perform vibratory movements of the body; the latter is described for the first time in anurans. Amplexus and oviposition occurred inside subterranean chambers. The temperature in closed chambers was lower than outside chambers, which may aid in reducing desiccation risks of eggs and tadpoles. Females were larger than males, but males had longer heads and shorter tibias, which may be related to digging. The study reinforces the importance of ongoing discoveries on anuran natural history.
Keywords: Chaco; natural history; sexual size dimorphism; subterranean chamber; vibratory movements